Clostridioides (Formerly Clostridium) difficile Infection During Hospitalization Increases the Likelihood of Nonhome Patient Discharge - Reveles, Kelly R (Clin Infect Dis, 2019)
BACKGROUND: Clostridioides (formerly Clostridium) difficile infection (CDI) is associated with significant morbidity and mortality, including frequent hospitalizations. However, the impact of CDI after hospital discharge is poorly understood. The purpose of this study was to assess patient discharge disposition and understand CDI-related risk factors for nonhome discharge. METHODS: Using a nationally representative database of Veterans Health Administration (VHA) patients (2003–2014) and a validation database from hospitalized non-VHA patients in Houston, Texas, admission and discharge disposition was obtained for patients with CDI and matched controls. Incidence of and clinical/microbiologic risk factors for nonhome discharge were assessed using these databases. RESULTS: A total of 15173 VHA patients with CDI and 48599 non-CDI control patients originally admitted from the community were included. Significantly more patients with CDI were discharged to a nonhome location compared with controls (18% vs 8%; P < .0001), most commonly hospice/death (12%) or nursing home/long-term care facility (6%). Results were confirmed using a propensity-matched analysis and a validation cohort of 1941 hospitalized patients with CDI in Houston, Texas. Age, comorbidities, severe CDI, and ribotypes F027, F001, and F053-163 were associated with a nonhome discharge (P < .05 for all). CONCLUSIONS: Hospitalized patients with CDI frequently required a higher level of medical care residence at discharge compared with non-CDI patients. Risk factors for discharge to a higher level of care included CDI disease severity and variables associated with recurrent CDI.